Pendaftaran Tanah Sistematis Lengkap (PTSL) Kepemilikan Atas Tanah - Widyastuti, Devitri; Lyanthi, Merline Eva (Journal Evidence Of Law, 2024)
PTSL is a program that aims to record and regulate land ownership in a comprehensive manner. This program facilitates land owners in securing their land rights through a complete and structured registration process. With PTSL, the government can provide stronger legal guarantees for land ownership, reduce land disputes, and increase community access to public services. The PTSL process involves systematic land surveying, mapping and registration. Surveys are conducted to identify land boundaries and ensure data accuracy. Mapping is carried out to record the location and soil characteristics in detail. Furthermore, the data is registered in a centralized database, allowing easy access and transparency in managing land information. Through PTSL, land owners obtain a valid and legally recognized ownership certificate. This certificate provides protection against claims or disputes over their land. Apart from that, PTSL also encourages investment in the property sector by providing legal certainty to investors. Implementing PTSL requires cooperation between the community, government and the private sector. The government is responsible for providing resources and regulations that support this program. The public needs to participate actively by providing the required information and supporting the registration process. Meanwhile, the private sector can provide technical and financial support in implementing the program. Overall, PTSL is an important step in efforts to improve land governance that is more efficient and transparent. By having a valid ownership certificate, people can feel safer and more protected in owning and managing their land.